AI-Driven Innovations in Enterprise Systems - Mustafa, Botan Shivan; Zeebaree, Subhi R. M. (International Journal of Scientific World, 2025)
This study investigates how Artificial Intelligence (AI) is transforming modern enterprise systems through intelligent automation, real-time analytics, and strategic decision-making. Drawing on a structured literature review of 21 recent studies, the research exam-ines AI’s integration across key domains, including ERP systems, enterprise architecture, cloud optimization, and human resource management. The findings reveal that AI significantly enhances operational efficiency, scalability, and business agility while ena-bling predictive modeling and adaptive workflows. However, the study also identifies critical challenges such as data governance, ethical transparency, integration complexity, and organizational readiness. By synthesizing theoretical foundations, empirical in-sights, and visual statistics, the review offers a holistic understanding of AI’s impact on enterprise innovation. It further highlights the need for strategic alignment, skill development, and explainable AI frameworks to ensure responsible and effective adoption. This work provides valuable guidance for organizations, researchers, and policymakers aiming to harness AI technologies for sus-tainable digital transformation and competitive advantage.